QUANTIFICATION OF VALSARTAN IN TABLETS BY VALIDATED UV-SPECTROPHOTOMETRIC METHOD - Tsvetkova, Dobrina Doncheva; Obreshkova, Danka Petrova; Yankov, Vladimir Petrov (IJRDO-Journal of Applied Science, 2019)
Angiotensin receptor blocker Valsartan is approved for treatment of I and II stage of hypertension. The aim of current study was the application of the validated UV-spectrophotometric method for determination of Valsartan by the external standard method in pharmaceutical dosage preparations (tablets) in 99.98 % ethanol at λmax = 252 nm and in methanol at λmax = 250 nm. UV-VIS diode array spectrophotometer was used. Data for Chauvenet’s criterion are lower than maximum permissible value (U = 1.73; N = 6), which is applied for the assessment of the need for the removal of sharply different results. All of the experimental results suit the respective confidence intervals. The analytical parameter repeatability for tablets is characterized by the uncertainty of the result, which includes standard deviation, relative standard deviation and confidential interval. All of the experimental results correspond to the respective confidence intervals at the confidence probability 98 %: Valsartan 160 mg tabl. (99.98 % ethanol): 159.69 mg ¸ 160.37 mg; Valsartan 160 mg tabl. (methanol): 158.51 mg ¸ 160.73 mg. Relative error is lower than 0.25 %. The validated method can be applied for the determination of Valsartan in pharmaceutical dosage forms.